Forecast of macroeconomic indicators for 2026 and strategic reforms in fiscal policy - Khusanov, Murodjon Sunnatullayevich; Azimjonov, Abdulvasit (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
This thesis describes the important factors that determine the economic stability and growth rate of each country, macroeconomic indicators and fiscal policy. The process of forming forecasts of macroeconomic indicators for 2026 is closely related, first of all, to the current economic situation of the country, national and global economic trends, as well as the state’s fiscal policy strategy.